2011
DOI: 10.1007/s10157-011-0547-5
|View full text |Cite
|
Sign up to set email alerts
|

Number of enlarged parathyroid glands might be a predictor of cinacalcet response in advanced secondary hyperparathyroidism

Abstract: These results indicate that the number of enlarged PTGs could predict therapeutic response of cinacalcet in patients with advanced SHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
10
0
3
Order By: Relevance
“…Similarly, a larger size parathyroid gland appeared to negatively influence the possibility of reaching the primary end point, although statistically insignificant. In line with our present finding, Yamamoto, et al23 recently found that two or more enlarged parathyroid glands might be a significant risk of poor response to cinacalcet treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, a larger size parathyroid gland appeared to negatively influence the possibility of reaching the primary end point, although statistically insignificant. In line with our present finding, Yamamoto, et al23 recently found that two or more enlarged parathyroid glands might be a significant risk of poor response to cinacalcet treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Second, there were no control groups. Third, total detected PTG number was not associated with “treatment failure”, although baseline PTG number has been found to be a predictor of response to cinacalcet . The reasons for this discrepancy, however, remain unclear.…”
Section: Discussionmentioning
confidence: 95%
“…However, some patients with refractory SHPT resistant to medical treatment including cinacalcet eventually require PTx [23]. A recent study has demonstrated that patients with two or more enlarged parathyroid glands had a significant risk of a poor response to cinacalcet treatment, and that the number of enlarged parathyroid glands could predict therapeutic response of cinacalcet in patients with advanced SHPT [24]. In the present study, we demonstrated that the expression of CaSR was significantly decreased in the larger glands (>500 mg) compared with that in the smaller glands (<500 mg) in both the conventional group and the cinacalcet group.…”
Section: Discussionmentioning
confidence: 99%